Epigenetic modifications in esophageal cancer: An evolving biomarker - Liu, Wen-Jian; Zhao, Yuan; Chen, Xu; Miao, Man-Li; Zhang, Ren-Quan (Frontiers in Genetics, 2023)
Esophageal cancer is a widespread cancer of the digestive system that has two main subtypes: esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EA). In the diverse range of cancer therapy schemes, the side effects of conventional treatments remain an urgent challenge to be addressed. Therefore, the pursuit of novel drugs with multiple targets, good efficacy, low side effects, and low cost has become a hot research topic in anticancer therapy. Based on this, epigenetics offers an attractive target for the treatment of esophageal cancer, where major mechanisms such as DNA methylation, histone modifications, noncoding RNA regulation, chromatin remodelling and nucleosome localization offer new opportunities for the prevention and treatment of esophageal cancer. Recently, research on epigenetics has remained at a high level of enthusiasm, focusing mainly on translating the basic research into the clinical setting and transforming epigenetic alterations into targets for cancer screening and detection in the clinic. With the increasing emergence of tumour epigenetic markers and antitumor epigenetic drugs, there are also more possibilities for anti-esophageal cancer treatment. This paper focuses on esophageal cancer and epigenetic modifications, with the aim of unravelling the close link between them to facilitate precise and personalized treatment of esophageal cancer.